Melanin-concentrating hormone promotes anxiety and intestinal dysfunction via basolateral amygdala in mice - He, Xiaoman; Li, Yuhang; Zhang, Nana; Huang, Jinfang; Ming, Xing; Guo, Ruixiao; Hu, Yang; Ji, Pengfei; Guo, Feifei (Frontiers in Pharmacology, 2022)
The limbic system plays a pivotal role in stress-induced anxiety and intestinal disorders, but how the functional circuits between nuclei within the limbic system are engaged in the processing is still unclear. In our experiment, the results of fluorescence gold retrograde tracing and fluorescence immunohistochemistry showed that the melanin concentration hormone (MCH) neurons of the lateral hypothalamic area (LHA) projected to the basolateral amygdala (BLA). Both chemogenetic activation of MCH neurons and microinjection of MCH into the BLA induced anxiety disorder in mice, which were reversed by intra-BLA microinjection of MCH receptor 1 (MCHR1) blocker SNAP-94847. In the chronic acute combining stress (CACS) stimulated mice, SNAP94847 administrated in the BLA ameliorated anxiety-like behaviors and improved intestinal dysfunction via reducing intestinal permeability and inflammation. In conclusion, MCHergic circuit from the LHA to the BLA participates in the regulation of anxiety-like behavior in mice, and this neural pathway is related to the intestinal dysfunction in CACS mice by regulating intestinal permeability and inflammation.